Prevalence and associated factors of underweight, overweight and obesity among women of reproductive age group in the Maldives: Evidence from a nationally representative study - Hashan, Mohammad Rashidul (PLoS One, 2020)
BACKGROUND: Global epidemiological transition across various countries have documented the coexistence of undernutrition and overnutrition. South Asian countries are facing this public health hazard in remarkable manner. To enrich the evidence and relation with women’s health in the Maldives, this study was undertaken to examine the prevalence and associated factors of underweight, overweight and obesity among reproductive age women. METHODS: This study was conducted utilizing data from the Maldives Demographic and Health Survey 2016–17. After presenting descriptive analyses, multivariable logistic regression analysis method was used to examine the prevalence and associations between different nutritional status categories. These were grouped based on the WHO recommended cut-off value and relevant socio-demographic determinants among reproductive age women. RESULTS: A total weighted sample of 6,634 reproductive age Maldivian women (15–49 years) were included in the analysis. The overall prevalence of overweight and obesity was 63%, while the underweight prevalence was 10%. The younger age group (15–24 years) had a higher prevalence of underweight (26%). On the other hand, an overweight and obesity prevalence of 82.6% was observed among the older age group (35–49 years). Regression analysis showed that residents of the North and Central Provinces, those in the higher quintiles of wealth index, married women and those with parity of more than two children, were all significantly negatively correlated to being underweight. Increased age, being married or separated/divorced/widowed and having more than three children was found to have a significant positive association with overweight and obesity. CONCLUSIONS: Maldives is facing nutritional transition and a major public health hazard demonstrated by the high burden of overweight and obesity and persistence of chronic problem of undernutrition. Surveillance of vulnerable individuals with identified socio-demographic factors and cost-effective interventions are highly recommended to address the persistent underweight status and the emerging problem of overweight/obesity.